2020
DOI: 10.1021/acs.jnatprod.0c00269
|View full text |Cite
|
Sign up to set email alerts
|

Psathyrins: Antibacterial Diterpenoids from Psathyrella candolleana

Abstract: Two skeletally novel tetracyclic diterpenoids, psathyrins A (1) and B (2), have been characterized from cultures of the basidiomycete Psathyrella candolleana. Their structures including absolute configurations were established by means of spectroscopic methods, as well as ECD calculations. They possess a novel 5/5/4/6-fuesd ring system, for which the biosynthetic pathway is proposed. Compounds 1 and 2 inhibited the growth of Staphylococcus aureus and Salmonella enterica.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Of them, two carbonyl signals at δ C 200.8 (s, C-5) and 205.4 (s, C-13), and four olefinic signals four two double bonds at δ C 150.2 (s, C-1), 162.5 (s, C-3), 130.5 (s, C-4), and 149.3 (s, C-14) occupied four degrees of unsaturation, suggesting a tricyclic backbone of 1 . All these data, as well as the literature survey [ 5 , 6 , 14 ], suggested that 1 should be a guanacastane diterpenoid characterized with a 5/7/6-fused ring system. Preliminary analysis of 2D NMR data (especially the HMBC data) revealed two α , β -unsaturated keto moieties in rings A and B, respectively (Fig.…”
Section: Resultsmentioning
confidence: 72%
See 3 more Smart Citations
“…Of them, two carbonyl signals at δ C 200.8 (s, C-5) and 205.4 (s, C-13), and four olefinic signals four two double bonds at δ C 150.2 (s, C-1), 162.5 (s, C-3), 130.5 (s, C-4), and 149.3 (s, C-14) occupied four degrees of unsaturation, suggesting a tricyclic backbone of 1 . All these data, as well as the literature survey [ 5 , 6 , 14 ], suggested that 1 should be a guanacastane diterpenoid characterized with a 5/7/6-fused ring system. Preliminary analysis of 2D NMR data (especially the HMBC data) revealed two α , β -unsaturated keto moieties in rings A and B, respectively (Fig.…”
Section: Resultsmentioning
confidence: 72%
“…It has a wide distribution on lawns or pastures in Europe and North America. Previous pharmacological studies indicated that the extracts of P. candolleana showed a marked anticlastogenic effect against DNA damage [1][2][3], while chemical investigations on this fungus have demonstrated guanacastane-type diterpenoids [4,5], which possess a unique 5/7/6 tricyclic backbone that have been found only in several fungal species. These diterpenoids have been detected to possess antibacterial and cytotoxic properties [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Psathyrelloic acid inhibits S. aureus but has no effect on P. aeruginosa and E. coli [46]. Similarly, psathyrins A and B, 2 tetracyclic diterpenoids, also inhibit weakly the growth of S. aureus without any effect toward P. aeruginosa [47]. While the first publication reports an MIC value, the second one mentions MIC 50 .…”
Section: Terpenoidsmentioning
confidence: 99%